MATHEMATICAL LITERACY ABILITY AND METACOGNITIVE CHARACTERISTICS OF MATHEMATICS PRE-SERVICE TEACHER - Christina M Laamena; Theresia Laurens (Jurnal Infinity, 2021)
This study aims to determine the characteristics of students' metacognition in solving mathematical literacy problems. The metacognitive traits explored are related to awareness in planning, monitoring, and evaluating the design of the thinking process used. The research method used is a mixed-method (sequential explanatory), which uses quantitative research results to conduct qualitative research. The research subjects were 80 early semester students who took the literacy test and chose six respondents representing the upper, middle, and lower groups, with two people in each group to be interviewed. The results showed that the mathematical literacy skills of prospective teachers were at a low level. Metacognitive characteristics that appear in the low group are (1) realizing that the solution of strategy is not right but not improved; (2) planning to develop a settlement strategy, but are not sure, (3) do not carry out the re-check process, and (4) do not believe what is being thought and do not understand the concept. Metacognitive traits in the middle group are (1) aware of what they are thinking, (2) consciously plan various strategies to improve thinking accuracy, but do not always use these strategies, (3) tend to monitor the thinking process, and (4) show tendency to master the basic mathematical concepts of the problems at hand.The characteristics of metacognition in the high group during problem-solving are (1) Using various strategies to demonstrate or improve the accuracy of thinking (sketching, drawing), (2) Analyzing the problem before solving it, and (3)Understanding and mastering the mathematical concepts that underlie the problem which is given.